2022
DOI: 10.1007/s00415-022-11472-6
|View full text |Cite
|
Sign up to set email alerts
|

New-onset Myasthenia Gravis after SARS-CoV-2 infection: case report and literature review

Abstract: We report the case of a 19-year-old female patient who developed Myasthenia Gravis 13 days after SARS-CoV-2 infection with positive RT-PCR testing. Her symptoms initially involved the oculo-bulbar district, but they gradually worsened in 3 months converting into a generalized form of Myasthenia Gravis complicated with a myasthenic crisis. A high level of anti-acetylcholine receptor antibodies was found in the serum, while anti-MuSK antibodies were negative; Repetitive Nerve Stimulation and Single-fiber Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…20 In a third case, while chest MRI showed no thymic abnormalities, histological analysis after thymic resection confirmed thymic hyperplasia. 27 The median time interval between COVID-19 and the clinical onset of MG was 17 days (range 5-56 days). In one case study, MG onset emerged post COVID-19 infection which followed an anti-SARS-CoV-2 booster dose vaccination.…”
Section: New-onset Mg Post Sars-cov-2 Infectionmentioning
confidence: 96%
See 2 more Smart Citations
“…20 In a third case, while chest MRI showed no thymic abnormalities, histological analysis after thymic resection confirmed thymic hyperplasia. 27 The median time interval between COVID-19 and the clinical onset of MG was 17 days (range 5-56 days). In one case study, MG onset emerged post COVID-19 infection which followed an anti-SARS-CoV-2 booster dose vaccination.…”
Section: New-onset Mg Post Sars-cov-2 Infectionmentioning
confidence: 96%
“…59 Our literature search identified 14 publications that reported 18 cases in the specified time frame (Table 1). [15][16][17][18][19][20][21][22][23][24][25][26][27][28] An additional publication that presented the case of an 86-year-old man with generalized muscle weakness, diplopia, ocular ptosis and dyspnoea in the subacute phase of COVID-19 was inconclusive. 60 For this patient, the diagnosis of MG was not supported by paraclinical investigations (i.e., no data were provided on RNS, SF-EMG or edrophonium/ neostigmine test, and AchR and MuSK antibodies were within the normal range).…”
Section: New-onset Mg Post Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myasthenia manifested as generalized muscle weakness in 11 patients; three presented with pure OMG, and only one presented with oculo-bulbar myasthenia. 74 Cases of myasthenia following covid-19 vaccination are much less reported than covid-19 infection, with only 4 cases reported, one of whom had been diagnosed with myasthenia 5 years before vaccination. 75 Given the small number of cases reported, there is no conclusive evidence that myasthenia is necessarily a complication of the COVID-19 vaccines, and the benefits of receiving the vaccine outweigh the potential risks.…”
Section: Myasthenia and Covid-19 Infection And Vaccinementioning
confidence: 99%
“…They surmised that the immune dysregulation created by infection with SARS-CoV2 resulted in histologically verified thymic dysfunction, resulting in the expression of anti-acetylcholine receptor antibodies. 59,60 The other systematic review reported the outcomes of the studies that it included. 61 They summarized that MGFA class greater than IV, 62 older age, and long-term use of corticosteroids 63 were associated with more severe COVID-19.…”
Section: Myasthenia Gravismentioning
confidence: 99%